World mortality in 2000 : life tables for 191 countries - Lopez, Alan D. (World Health Organization, 2002)
Reliable information on the numbers of people who die in various countries according to age and sex is a fundamental requirement for setting health priorities and evaluation health programmes. Mortality levels and trends have been monitored in some countries for centuries, while in others, particularly in Sub-Saharan Africa, little is currently known about adult mortality. This uncertainty has increased in the 1990s due to the HIV/AIDS epidemic, precisely at the time when priority setting in health requires reliable information on mortality levels in countries and regions. This book provides d.